Agama dan Ideologi - Donatus Sermada (Perspektif, 2008)
The description of the freedom of how to practice the religion in Indonesia as the author reflects on it in the light of the official documents is a stepping stone to go deeper into the important insight to the relationship between religion and ideology. The freedom of practicing the religion should be based on the correct understanding of the essential difference between religion and ideology. The author attempts to elaborate both of them separatedly in order to gain the genuine insight to the basic essential difference between them. The essence of religion is reflected in the line of tracing linguistic meaning of two words "agama" and "religion" back to the traditions which have provided them the frame of understanding to the meaning of these two terms. In a similar way, the meaning of ideology is depicted in the historical context of its use for the certain interest and authority. The last part of this article shows up the author's effort to pound on the unavoidable and proper relationship between religion and ideology by pointing out the process of the ideologization of religion we have to avoid of. The process of ideologization of religion can lead us to the misunderstanding of these two fields -religion and ideology as if both of them were the same.